Regulating the Single-Mode Lasing Intensity of Semiconductor Lasers Without Wavelength Shift - Yang Wang; Xiaoyan Wu (IEEE Photonics Journal)
A simple method to regulate the single-mode lasing intensity of semiconductor lasers without wavelength shift is demonstrated in this paper. The basic component is a digital micro-mirror device (DMD), which can be taken as an adjustable two-dimensional grating by its special structure. The lasing peak wavelength and peak intensity are respectively regulated by the DMD angular position and the DMD setting. The lasing peak wavelength could be tuned over by rotating the DMD. Meanwhile, the lasing peak intensity could be regulated by the DMD setting, which generates optical feedback digitally. The regulating speed is very high (up to 10 kHz) and has no wavelength shift in the lasing mode, which is more stable and faster than the conventional method.